Declaration of Buenos Aires on the situation of Ecuador - Suramericanas, Unión de Naciones (2013)
Extraordinary Meeting of the Council of Chiefs and Heads of State and Government of the UNASUR, in Palacio de San Martin, Buenos Aires, Argentina on October 1, 2010.